New molecular data on subcutaneous Philornis (Diptera: Muscidae) from southern South America suggests the existence of a species complex - Quiroga, Martin Anibal (2016)
The taxonomic identification of species in the genus Philornis Meinert (Diptera: Muscidae) has been based primarily upon analysis of morphological characters. However, relying solely on morphology has led to frequent species misidentification. This has been empirically demonstrated when specimens identified morphologically as Philornis seguyi have been reclassified as Philornis torquans based on DNA sequences of the second ribosomal internal transcribed spacer (ITS2), showing that the morphologic distinction between these 2 species is extremely challenging. Herein, new molecular data on specimens assigned to P. torquans and P. seguyi from the type locality of P. seguyi (Misiones province, Argentina) were analyzed. The ITS2 sequences obtained differed from those previously reported for Philornis, increasing to 3 the number of documented genotypes of flies morphologically indistinguishable from P. torquans. These results strongly suggest that subcutaneous Philornis spp. from southern South America could represent a species complex (P. torquans complex).